Government Policies and Ethnical Diversity Under Multiculturalism: The Study of Pohuwato Regency - Wantu, Sastro M (KOMUNITAS: International Journal of Indonesian Society and Culture, 2017)
This paper describes the construction of ethnic integration in Pohuwato local government policies which is supported by community under Bhinneka Tunggal Ika (Unity in Diversiy) and multiculturalism. This research employed qualitative approach with the aim of tracing and analyzing social harmony from various ethnicities existing in society and government policy Pohuwato Regency. The instruments of the study included data, facts and concepts that were relevant. This study aimed to see the problem of segregation within societies by primordial groups to solve ethnic integration in which ethnic groups are bound together. There are two regional policies (1) controlling inter-ethnic relations and constructing the model of Gorontalo community as an important element of social, cultural and political aspect which uphold openness and tolerance; and (2) using deliberative public space in order to achieve harmonious atmosphere between public (community) with the government in protecting the diversity. Therefore, it can be concluded that ethnic communities residing in Pohuwato Regency are bound to unite by the desire to improve new and better lives between immigrants and local communities. This desire becomes a symbol of unity based on mutual respect for different values to achieve the integration or unity of multicultural ethnic groups.